High diversity of RNA viruses in rodents, Ethiopia - Meheretu, Yonas; Cížková, Dagmar; Těšíková, Jana; Welegerima, Kiros; Tomas, Zewdneh; Kidane, Dawit; Girmay, Kokob; Schmidt-Chanasit, Jonas; Bryja, Josef; Günther, Stephan; Bryjová, Anna; Leirs, Herwig; et al. (Emerging infectious diseases, 2012)
We investigated synanthropic small mammals in the Ethiopian Highlands as potential reservoirs for human pathogens and found that 2 rodent species, the Ethiopian white-footed mouse and Awash multimammate mouse, are carriers of novel Mobala virus strains. The white-footed mouse also carries a novel hantavirus, the second Murinae-associated hantavirus found in Africa.
Keywords: Ethiopia; RNA virová; Disease Reservoirs; Humans; Phylogeny; RNA Virus Infections; Rodentia; Molecular Sequence Data; molekulární sekvence - údaje; zdroje nemoci; RNA-viry; lidé; zvířata; myši; Hantavirus; infekce RNA viry; Mice; Etiopie; RNA Viruses; fylogeneze; hlodavci; nemoci hlodavců; RNA, Viral; Animals; Rodent Diseases; Orthohantavirus